A scoping review of nutrition education interventions to improve competencies, lifestyle and dietary habits of medical students and residents. (2nd March 2023) - Mogre, Victor; Amoore, Bright Yammaha; Gaa, Patience Kanyiri
Abstract: We reviewed the available research and gave an overview of the effects of nutrition education interventions (NEIs) on medical students' and residents' knowledge of nutrition, attitudes towards nutrition care, self-efficacy, dietary practices and readiness to offer nutrition care. From 28 May through 29 June 2021, we searched Google Scholar, PubMed, ProQuest, Cochrane and ProQuest to retrieve 1807 articles. After conducting de-duplication and applying the eligibility criteria and reviewing the title and abstract, 23 papers were included. The data were descriptively and narratively synthesised, and the results were displayed as frequencies, tables and figures. Twenty-one interventions were designed to increase participants' knowledge of nutrition-related topics, and eighteen studies found that nutrition knowledge had significantly improved post-intervention. Only four of the eleven studies that reported on attitudes about nutrition post-intervention showed a meaningful improvement. The self-efficacy of participants was examined in more than half of the included studies ( n 13, 56⋅5 %), and eleven of these studies found a significant increase in the participants' level of self-efficacy to offer nutrition care post-intervention. At the post-intervention point, seven interventions found that dietary and lifestyle habits had significantly improved. The review demonstrated the potential of NEIs to enhance participants' dietary habits and nutrition-related knowledge, attitudes and self-efficacy. Reduced nutrition knowledge, attitude and self-efficacy scores during the follow-up, point to the need for more opportunities for medical students and residents to learn about nutrition after the intervention.